Advertisement Remove all ads

Solve X(X + 1) + (X + 2)(X + 3) = 42 - Mathematics

Sum

Solve x(x + 1) + (x + 2)(x + 3) = 42

Advertisement Remove all ads

Solution

x(x + 1) + (x + 2)(x + 3) = 42

`=> x^2 + x + x^2 + 3x + 2x + 6 - 42 = 0`

`=> 2x^2 + 6x - 36 = 0`

`=> 2x^2 + 12x - 6x - 36 = 0`

`=> 2x(x + 6) - 6(x + 6) = 0`

=> (x + 6)(2x - 6) = 0

if x + 6 = 0 or 2x - 6 = 0

then x = -6 or x = 3

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 5 Quadratic Equations
Exercise 5 (E) | Q 17.1 | Page 67
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×